Respuesta de las plántulas del rábano (Raphanus sativus L.) a diferentes concentraciones de nitrógeno amoniacal en ausencia y presencia de silicio - Olivera Viciedo, Dilier [UNESP]; de Mello Prado, Renato [UNESP]; Lizcano Toledo, Rodolfo [UNESP]; Nascimento dos Santos, Luiz Cláudio [UNESP]; Peña Calzada, Kolima (My University, 2017)
There are unknown thresholds about the effects of ammonia toxicity in the cultivation of radish and its prejudice is higher in the root than in the aerial part, been the use of silicon an alternative to mitigate this toxicity. The objective was to evaluate the response of radish crop to different concentrations of an ammonium nutrient solution in the absence and presence of silicon under greenhouse conditions. After 30 days of germination were evaluated photosynthesis, green color index, stomatal conductance, transpiration, leaf area, tap root diameter, dry matter accumulation of nitrogen and silicon in shoot parts and roots respectively. Ammonia toxicity in radish decreased photosynthesis, transpiration, and stomatal conductance, having greater prejudice in the dry matter accumulation of root and aerial part, this effect was mitigated with the presence of silicon in the nutrient solution.
Response of radish seedlings (Raphanus sativus L.) to different concentrations of ammoniacal nitrogen in absence and presence of silicon
Keywords: Abiotic stress; Beneficial element; Nitrogen; Nutrient solution; Vegetable